2019
DOI: 10.1111/ajt.15497
|View full text |Cite
|
Sign up to set email alerts
|

SIRPα/CD47 axis controls the maintenance of transplant tolerance sustained by myeloid-derived suppressor cells

Abstract: Myeloid‐derived suppressor cells (MDSC) are a heterogeneous population of immature hematopoietic precursors known to suppress immune responses. Interaction of SIRP alpha (SIRPα), expressed by myeloid cells, with the ubiquitous receptor CD47 is an important immune checkpoint of the innate response regulating macrophages and dendritic cells functions. We previously described that MDSC expressing SIRPα accumulated after transplantation and maintained kidney allograft tolerance. However, the role of the SIRPα/CD47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 75 publications
(109 reference statements)
0
25
0
Order By: Relevance
“…In the context of organ transplantation, the Lakkis laboratory demonstrated that blocking SIRPa or CD47 with monoclonal antibodies induced graft dysfunction and rejection. Blocking of SIRPa-CD47 interaction results in MDSC differentiation into myeloid cells overexpressing MHC class II, CD86 costimulatory molecule and increased secretion of macrophage-recruiting chemokines leading to loss of tolerance (141). However, a donor allograft with a SIRPa molecule that is mismatched with CD47 leads causes monocytic cell activation and initiation of the immune response to the transplanted organ (135).…”
Section: Macrophages and Rejectionmentioning
confidence: 99%
“…In the context of organ transplantation, the Lakkis laboratory demonstrated that blocking SIRPa or CD47 with monoclonal antibodies induced graft dysfunction and rejection. Blocking of SIRPa-CD47 interaction results in MDSC differentiation into myeloid cells overexpressing MHC class II, CD86 costimulatory molecule and increased secretion of macrophage-recruiting chemokines leading to loss of tolerance (141). However, a donor allograft with a SIRPa molecule that is mismatched with CD47 leads causes monocytic cell activation and initiation of the immune response to the transplanted organ (135).…”
Section: Macrophages and Rejectionmentioning
confidence: 99%
“…Furthermore, intrasplenic infusion of CD47‐deficient allogeneic hepatocytes resulted in accelerated rejection of donor‐matched skin grafts, whereas CD47‐competent hepatocytes enhanced skin allograft survival that was associated with reduced alloreactive T cell responses, enhanced production of regulatory cytokines, IL‐4 and IL‐10, as well as significant expansion of MDSC 27 . Indeed, CD47 was shown to play a critical role in the expansion and regulatory function of MDSC in a costimulatory blockade‐induced tolerance to kidney allografts 71 . The blockade of CD47/SIRPα pathway in this model resulted in the rejection of long‐term tolerant kidney grafts, which was associated with the overexpression of MCP‐1 and inflammatory macrophage signature.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, MDSC have been demonstrated as an essential player in maintenance of transplantation tolerance in many types of tissue or organ transplantation, such as corneal penetrating keratoplasty, 4–6 skin transplantation, 7 bone marrow transplantation, 8 kidney transplantation, 9,10 pancreatic islets transplantation, 11,12 and heart transplantation 13,14 . A cell therapy involving adoptive transfer of MDSC is therefore considered as a valuable novel candidate therapeutic approach to prolong graft survival 15,16 .…”
Section: Introductionmentioning
confidence: 99%